PENDIDIKAN KETERAMPILAN SOSIAL ANAK USIA DINI DI RUMAH - Sit, Masganti; Octavia, Cindi; Nur Jannah, Siti; Dwita Putri, Dhea (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
Social skills education for children at home has an important role in shaping children's character and ability to interact with their environment. Social skills include the ability to communicate, empathy, cooperation, self-control and conflict resolution, which are the main provisions for facing social challenges in the future. The home environment as the first place where children learn has a big influence on the formation of these skills. The role of parents is very significant in instilling these values through positive parenting, good role models, and opportunities to practice social skills in daily activities. This research aims to explain the importance of social skills education at home, strategies that can be implemented by parents, and their impact on child development. The study results show that a consistent and loving approach from parents can significantly improve children's social skills, thereby preparing them to become socially and emotionally competent individuals in the future. Early childhood social skills need to be identified from the start to prevent negative behavior. Therefore, this research aims to explore how children's social skills are educated at home. Referring to the research objectives, the qualitative approach used the method of interviewing three parents regarding children's social skills education at home and aged 5-6 years. The research was located in one of the Tanjung Morawa villages. Data was collected through observation, interviews and documentation studies.